ANALISIS KEMAMPUAN MANAJERIAL KEPALA SMA NEGERI I PANGKAJENE KABUPATEN PANGKEP - Rosdiana, Rosdiana (Pascasarjana Universitas Negeri Makassar, 2015)
The purpose of this study was to determine: (1) overview of managerial skill of principal at SMAN 1 Pangkajene in Pangkep; (2) factors that support the managerial skill of principal at SMAN 1 Pangkajene in Pangkep; (3) factors that hinder managerial skill of principal at SMAN 1 Pangkajene in Pangkep. This is a qualitative descriftive research , data source were the principal, the vice-principal, the supervised and the head of administration. Techniques of data collection were by interview, observation and documentation. Data validity was conducted throught the extension of the observation, triangulation and member checks. The result show that the principal of SMAN 1 Pangkajene in Pangkep has a good managerial competence based on four managerial function include: planning, organizing, actuating and supervision. The supporting factors of principal’s managerial competence include internal factors, namely: the principal human resources, the ability to lead/managing, educational qualification and personality of the principal’s. The external factors include support from local government, local community ant the support of the entire school community. Where as, the inhibiting factor includes the limited funding and the participation of parents in the form of funds which is lack since the free education program in schools.